Physiological and biomechanical analyses of a 200 m all-out front crawl - Franken, Marcos; Jesus, Kelly de; Miranda, Vitória; Jesus, Karla de (Acta Scientiarum. Health Sciences, 2024)
This study aimed to analyze the effort effects of laps on general stroke kinematics and associate the peak oxygen uptake (V̇O2peak) with all-out 200-m front crawl time. Fourteen regional-level swimmers (age 16.14 ± 2.68 years; height 1.65 ± 0.08 m; body mass 58.17 ± 7.76 kg) performed an all-out 200 m front crawl. Oxygen consumption (V̇O2) was measured post-all-out 200 m trial to assess physiological variables and stroke mechanics was assessed based on the time to perform 10 m and time to perform three complete arm stroke cycles. The 1st lap had a higher stroke rate (SR) than the 3rd lap (44.73 vs. 40.82 cycles⋅min-1; p = 0.04). The 1st lap showed a higher mean swimming speed (SS) than the following laps (1.45 ± 0.10 vs. 1.35 ± 0.11 vs. 1.30 ± 0.11 vs. 1.28 ± 0.13 m⋅s-1; p < 0.01) and the 2nd was greater than the 4th lap (p < 0.05). The swimming index (SI) was smaller and greater in the 3rd lap compared to the 1st and 4th laps (2.60 ± 0.65 vs. 2.97 ± 0.71 vs. 2.43 ± 0.50 m2⋅s-1⋅cycles-1), respectively. There was moderate and inverse coefficient of correlation between the V̇O2peak and 200-m time (rho = -0.653; p < 0.05). Our findings suggest that V̇O2peak values should be assessed in post 200-m all-out effort due to the strong shared variance with performance and a pacing strategy should be adopted during the race to avoid detrimental effects of fatigue.